Utilization of Varmam Therapy in Improving Quality of Life (QoL) in patients with Cervical Dystonia- A case study - Shweta Tiwari (Indian Journal of Integrative Medicine, 2024)
Cervical Dystonia commonly called ’Spasmodic Torticollis’ is a neurological disorder that causes involuntary muscle contractions, spasms, pain and tremors in the neck region. Sagana Vatham is one among 80 vatha disease mentioned in the Siddha text book of Siddhar Yugi. This disease affects the neck & upper extremities with some of its signs and symptoms bearing a resemblance to cervical dystonia symptoms. It is seen that different Complementary and Alternative Medicines (CAMs) have provided relief in cases of CD. Siddha vaidyam is another alternative therapy used in such disorders. A 56-year-old male from Hyderabad a K/C/O Cervical Dystonia reported to the Chakrasiddh with chief complaints of pain and involuntary movements to the right side of the neck since 2 1/2 yrs. He was given Varma therapy like Varma Elakku Muraigal (Varma Relieving Methods) and Varma Thadavu Muraigal (Varma Massage Methods) to decrease pain and spasms, myofascial release and stretching, to decrease dyskinesia. The total treatment was given for 25 sessions in 6 months span with gaps in between. This study aimed to examine the effects of Siddha therapy on pain, spasms, and dyskinesia and to identify possible improvements in the quality of life (HRQoL) of the patient. NRS was used for pain at each session. Disease-specific HRQoL was assessed by using the Cervical Dystonia Impact Profile-58 questionnaire (CDIP-58). Positive outcomes were exhibited after 25 sessions in the frequency of pain and spasms and holding the neck in the centre for 1 hour which was just <5 mins earlier. The pain (NRS) was markedly reduced from a 7/10 score to 2/10. CDIP-58 scores, disease-specific HRQoL, showed a significant improvement in all parameters after 25 sessions of treatment.